2002
DOI: 10.1080/00185860209597991
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Certified Nursing Assistants: A Major Problem for Long-term Care Facilities

Abstract: The increasing number of aging Americans who will need long-term care, coupled with the need to keep this care affordable, represents a formidable challenge to the healthcare system. Some response must be made to address what will soon become immediate need. A significant part of the approach to this problem lies in making long-term care as efficient, cost effective, and affordable as possible. Reducing turnover of certified nursing assistants (CNAs) will help achieve these goals. This article discusses the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…A study conducted in South Carolina by Fitzpatrick concluded that 12 diverse long term care facilities demonstrated an average turnover rate of 65 percent, with a range between 53 and 82 percent (Fitzpatrick, 2002). These statistics are concerning as they allude to a potential shortage of employees in the LTC sector although it is not clear whether or not health care workers change jobs within the long term care sector or leave it entirely (Black, 2015).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in South Carolina by Fitzpatrick concluded that 12 diverse long term care facilities demonstrated an average turnover rate of 65 percent, with a range between 53 and 82 percent (Fitzpatrick, 2002). These statistics are concerning as they allude to a potential shortage of employees in the LTC sector although it is not clear whether or not health care workers change jobs within the long term care sector or leave it entirely (Black, 2015).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The Paraprofessional Health Care Institute (2001) estimates CNA turnover costs the industry $2.5 billion per year (Tilden, Thompson, Gajewski, & Bott, 2012). One study on CNA turnover puts this shortage at 200,000 nationwide, however that was done nearly two decades ago (Fitzpatrick, 2002).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Turnover among CNAs in LTC reached critical proportions in 1999 [4]. Parsons, et al found 30% of the CNA workforce leaves LTC positions within 4.6 years of employment due to dissatisfying factors [5].…”
Section: Certified Nursing Assistants and Job Satisfactionmentioning
confidence: 99%
“…however, this minimal training in nursing support roles no longer equips these key front-line staff with the skills to meet the complex needs of the current resident population of LtC homes (Stolee et al 2005). there is much support for increased education for LtC staff (american geriatrics Society and american association for geriatric Psychiatry 2003;fitzpatrick 2002). in addition to ongoing staff education, LtC homes often turn to continuing education (Ce) when faced with compliance citings related to Ministry of health standards, a critical incident, accreditation, policy planning, or continuous quality improvement (CQi) related to prevention, risk management or enhancement of quality of life.…”
Section: Getting a Bigger Bang For Your Buck: A Collaborative Approacmentioning
confidence: 99%